You can solve it by replacing the Y in the 2nd equation with the solved Y in the first.
4x + 2(3x-15)= 22
that should give you...
4x + 6x - 30 = 22
then combine like terms...
10x - 30 = 22
now we need to get X alone so add 30 to each side....
10x = 52
now divide both sides by 10..
X = 52\10
both are divisible by 2...
X = 26\5
you should be done unless you need Y as well then go back to the first and plug in what you found for X...
Y = 3(26รท5)- 15
and that should give you Y.
a 2nd method you can make your own answer by making x = 0 ..
Y= 3(0) -15
Y= -15
now put that in the 2nd for Y...
4x+ 2(-15) = 22...
4x-30= 22
add 30 to both sides..
4x = 52
divide by 4....
X = 13
now take this to the first for x...
Y= 3(15) - 15
Y = 30
you can check your work by plugging in the two on top and see if the final is the same..
30 = 3(15) - 15
the 2nd way is faster though of course..
anyway X= 13 Y= 30